2008
DOI: 10.3174/ajnr.a0918
|View full text |Cite
|
Sign up to set email alerts
|

Vertebroplasty in Multiple Myeloma: Outcomes in a Large Patient Series

Abstract: BACKGROUND AND PURPOSE:Despite the literature supporting the efficacy of vertebroplasty for treatment of osteoporotic vertebral compression fractures, few reports exist documenting its use in the treatment of compression fractures in multiple myeloma patients. Accordingly, we sought to characterize the imaging characteristics, clinical course, and outcomes in myeloma patients treated with vertebroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(75 citation statements)
references
References 31 publications
5
68
0
2
Order By: Relevance
“…In conclusion, this study, in line with other reported retrospective series [16,20], confirmed that PV is a safe ad effective treatment for of painful VCFs resulting from the progression of MM disease. PV produced pain relief and recovery from moderate to total disability, both of which were maintained during long-term follow-up.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In conclusion, this study, in line with other reported retrospective series [16,20], confirmed that PV is a safe ad effective treatment for of painful VCFs resulting from the progression of MM disease. PV produced pain relief and recovery from moderate to total disability, both of which were maintained during long-term follow-up.…”
Section: Discussionsupporting
confidence: 90%
“…Kyphoplasty (KP) [19] uses an inflatable bone tamp generally introduced bilaterally through a larger cannula before PMMA injection to restore vertebral height and to decrease PMMA leakage. Preliminary retrospective studies have demonstrated the effectiveness of PV [16,20] and KP [21,22] in controlling pain and improving the quality of life of patients with painful MM of the spine. Few studies have prospectively analyzed the clinical outcomes achieved by PV [23] and KP [17] in relatively small series of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation, typically in low doses administered in few fractions, can lead to rapid improvement in pain but should be avoided in newly diagnosed patients in nonurgent circumstances, particularly when multiple lesions are presents and large fields are required. Vertebroplasty and kyphoplasty are often employed in the treatment of vertebral fracture and are associated with short term pain improvement [95][96][97].…”
Section: Do Manage Painmentioning
confidence: 99%
“…Several reports have focused on the use of vertebroplasty, particularly in the treatment of osteolyses and compression fractures in myeloma patients (22)(23)(24)(25)(26)(27)(28)(29)(30). Conservative pain management with bed rest, bracing, bisphosphonates and analgesic drugs is often not sufficient to control the acute and chronic spinal pain accompanying pathologic fractures in myeloma patients.…”
Section: Discussionmentioning
confidence: 99%
“…McDonald et al (22) presented clinical outcome data from 67 MM patients undergoing vertebroplasty over a 7-year period. They reported a statistically significant improvement on the Roland-Morris Disability Questionnaire, as well as in the VAS values that their patients documented immediately after the procedure and during the follow-up period of up to 1 year.…”
Section: Discussionmentioning
confidence: 99%